The CARICOM Regional Transformation Programme for Agriculture : the hot pepper industry in CARICOM : competitiveness & industry development strategies - Singh, R. H. (UWI. Department of Agricultural Economics and Extension St. AugustineTT, 2007)
Presents a profile of the pepper growing areas in CARICOM and an industry profile for each country. Highlights the market intelligence reports and provides four analytical reports.